2013
DOI: 10.1597/11-150
|View full text |Cite
|
Sign up to set email alerts
|

Congenital and Postnatal Factors Inducing Malocclusions in Japanese Unilateral Cleft Lip and Palate Patients—Determination Using Logistic Regression Analysis

Abstract: Objective : To assess the congenital and postnatal factors that affect degree of malocclusion in patients with unilateral cleft lip and palate using multivariate statistical analysis. Design : Retrospective study. Patients : All information on 135 subjects with unilateral cleft lip and palate was obtained from an oral examination and radiograph at the initial examination at an orthodontic clinic and from surgical records. Plaster models were taken before orthodontic treatment. The ages of the subjects ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
(40 reference statements)
2
27
1
Order By: Relevance
“…In our study, we evaluated the Millard and modified Millard techniques for cheiloplasty and our results showed unfavorable outcome with the modified Millard technique for cheiloplasty. Others authors [16, 20, 21, 29] have also found significant differences. Kajii et al [20] and Alam et al [21] evaluated Japanese patients with UCLP and found that the modified Millard technique with vomer flap had a poor effect on DAR; this study used a different index.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In our study, we evaluated the Millard and modified Millard techniques for cheiloplasty and our results showed unfavorable outcome with the modified Millard technique for cheiloplasty. Others authors [16, 20, 21, 29] have also found significant differences. Kajii et al [20] and Alam et al [21] evaluated Japanese patients with UCLP and found that the modified Millard technique with vomer flap had a poor effect on DAR; this study used a different index.…”
Section: Discussionmentioning
confidence: 78%
“…Others authors [16, 20, 21, 29] have also found significant differences. Kajii et al [20] and Alam et al [21] evaluated Japanese patients with UCLP and found that the modified Millard technique with vomer flap had a poor effect on DAR; this study used a different index. However, in another study, the Millard technique showed tremendous results with narrow clefts, whereas the Tennison technique showed more flexibility with wide clefts [29].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Extensive research efforts have predicted the treatment outcomes of unilateral cleft lip and palate cases based on the specific indices available. [4][5][6][7][8][9][10] We recommend the development of an index which incorporates all growth planes as well as focuses on the cephalometric landmarks. It would enable surgeons to predict the outcome of all types of clefts and plan interventions accordingly.…”
Section: Is Outcome Based Cleft Research Leading Somewhere?mentioning
confidence: 99%
“…They used the 5-year-old index and Goslon Yardstick for the evaluation of dental arch relationship and suggested that Modified Millard cheiloplasty is more favorable than vomer flap. Kajii et al (2013) [3] , analyzed subjects with unilateral cleft lip and palate (UCLP). The Goslon Yardstick was used to assess the dental arch relationship.…”
mentioning
confidence: 99%